The application of microphotometry to the indirect immunofluorescent antibody technique using the human gastric parietal cell antigen–antibody system - Irvine, W. J. (1969)
This paper is an account of our experience in the use of the Leitz microphotometer equipment in the attempt to quantitate the degree of specific fluorescence in the indirect immunofluorescent antibody technique using the human gastric parietal cell antigen–antibody system. The main limitation of the equipment at present is the variability of the HBP 200 W lamp. This fact, together with the biological variation within the tissue section, makes multiple readings necessary. The method is, therefore, time consuming and perhaps mainly applicable to the investigation of standardization of the immunofluorescent technique itself and of the reagents used rather than the quantitation of results obtained in a routine manner using an accepted technique.